Asylum and Madness: Revolution within the Mexican Revolution in Cristina Rivera Garza’s Nadie me verá llorar (Anclajes, 2012)
Interweaving history and fiction, Cristina Rivera Garza’s novel, Nadie me verá llorar (1999), traces the story of the asylum La Castañeda during the first decades of the twentieth century with the purpose of critically examining a new emerging discipline system in the process of construction of a “good citizen.” Yet, through the representation of a “demented” woman who does not conform to the nation’s modernization project, this novel also offers different angles to read the Mexican Revolution. Performative madness, as a strategy of resistance of so-called pathological subjects to domestication, can be interpreted as a revolutionary expression that has been silenced in the hegemonic history of the revolution. Thus, rather than it just being a site of confinement and control, the asylum becomes a battlefield of constant negotiation of power and language. Breaking with conventional ideas of history, Rivera Garza demonstrates that the defiance of disciplined civic life constitutes another form of revolution within the Mexican Revolution.
Keywords: Asylum; Cristina Rivera Garza; Mexican Revolution; Mexican Literature; madness